Diversidade taxonômica e funcional de Ostrácodes pleustônicos (Crustacea, Ostracoda) em sistema rio-planície de inundação. - Pinto, Márian Bozzo de Oliveira (2017)
In the last decades, the functional diversity approach has been evaluated in several aquatic communities, except on the ostracods community, due to the complexity of the analyzes . On the other hand, studies on taxonomic diversity and abundance of ostracods have been extensively explored. In this way, the objective of this work was to evaluate the taxonomic and functional diversity of ostracods associated with Eichhornia crassipes of the river-floodplain system of the Upper Paraná River, Brazil. The hypothesis tested was that the greater taxonomic and functional diversity of ostracods occurs in environments that are more heterogeneous. The taxonomic and functional diversity of the ostracods followed the same pattern in the lotic and lentic environments, corroborating with the functional properties, which postulate that there is a positive relation between the diversities. Both diversity indexes showed that the ostracods community differs in lotic and lentic environments, owing to the environmental peculiarities that allow the permanence of specific communities adapted to such conditions. High diversity of ostracods in lentic environments corroborated the hypothesis that the greater environmental heterogeneity harbor high species diversity, with different ecological requirements or niche amplitudes. The use of functional traits proved to be effective in evaluating the ostracods community as well as the taxonomic diversity.